Transformation of Borrelia burgdorferi. Issue 3 (4th March 2021) - Seshu, J.; Moy, Brian E.; Ingle, Taylor MacMackin
Abstract: Transformation techniques used to genetically manipulate Borrelia burgdorferi, the agent of Lyme disease, play a critical role in generating mutants that facilitate analyses of the role of genes in the pathophysiology of this bacterium. A number of borrelial mutants have been successfully isolated and characterized since the first electrotransformation procedure was established 25 years ago (Samuels, 1995). This article is directed at additional considerations for transforming infectious B. burgdorferi to generate strains retaining the plasmid profile of the parental strain, enabling analysis of transformants for in vitro and in vivo phenotypes. These methods are built on previously published protocols and are intended to add steps and tips to enhance transformation efficiency and recovery of strains amenable for studies involving colonization, survival, and transmission of B. burgdorferi during the vector and vertebrate phases of infection. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of stock cultures, propagation of spirochetes, and analysis of plasmid profiles Basic Protocol 2 : Preparation of plasmid and linear DNA templates for transformation Basic Protocol 3 : Transformation of B. burgdorferi Basic Protocol 4 : Antibiotic selection of borrelial transformants Basic Protocol 5 : Isolation of borrelial transformants in agar overlays Basic Protocol 6 : Complementation of mutant borrelial strains in cis or in trans